Characteristics of Porous Starch from Lotus Seeds Using Dextranase: Protection and Sustained Release of Proanthocyanidins - Yuying Wang; Ming’ao Wang; Weihong Jiang; Siying Li; Siyu Liu; Mingwang Liu; Mingsheng Lyu; Shujun Wang (Foods)
Porous starch, known for its large specific surface area due to internal pores, exhibits excellent adsorption capabilities. In this study, we successfully produced porous starch from lotus seeds using dextranase and conducted a comprehensive analysis of its surface morphology, crystalline structure, pasting behavior, and adsorption characteristics. The enzymatic treatment resulted in the development of a pore structure on the lotus seed starch (LS) surface without altering its crystalline structure, as confirmed by Fourier transform infrared spectroscopy and X-ray diffraction. The oil and water absorption capacities of the porous starch increased by 14% and 27%, respectively. Differential scanning calorimetry indicated a higher pasting temperature for the porous starch. This starch exhibited remarkable drug-carrying capabilities, absorbing up to 18.23 mg/g of proanthocyanidins and significantly shielding them from UV damage. In vitro release tests in simulated intestinal fluid revealed that the encapsulated proanthocyanidins (PC) achieved nearly complete release. These results underscore the potential of LS as a drug carrier and provide valuable insights for developing innovative intestinal drug delivery systems.